(untitled) - Vanderkerckhove, Karen (Alphen aan den Rijn, The Netherlands, 2002)
In the course of the presentation, a thorough analysis of legal scholarship in the area leads to numerous applications of the various theories and doctrines that can be brought to bear on veil piercing cases. In addition, an in-depth discussion of the international dimension of corporate veil piercing focuses on the question of which laws should govern the liability of a parent corporation for the debts of its subsidiary. Throughout, the author’s clear insight into the substantive law of veil piercing sheds light on traditional misconceptions in the conflict of laws on the issue. She also details initiatives undertaken by various international bodies, including the United Nations, the Organization for Economic Cooperation and Development, the European Union, the International Court of Justice, and the International Labour Organization.
Keywords: Corporate veil; European Union countries